Novel hemagglutinin-binding sulfated oligofucosides and their effect on influenza virus infection. Issue 54 (19th June 2018) - Kosono, Shuhei; Kasai, Akihiro; Komaba, Sumika; Matsubara, Teruhiko; Sato, Toshinori; Takahashi, Daisuke; Toshima, Kazunobu
Abstract : A purpose-designed trimer10 possessing three sulfated oligofucoside moieties of5 effectively bound to hemagglutinins and inhibited influenza virus infection. Abstract : Among a series of chemically synthesized fucoidan derivatives (1–9 ), 5 was found for the first time to bind to influenza virus hemagglutinins (HAs) and inhibit hemagglutination activity. In addition, a designed C3 -symmetric tripodal ligand10, synthesized with three sulfated oligofucoside moieties of5, exhibited much greater hemagglutination inhibition activity than5 . A plaque assay using MDCK cells demonstrated that10 effectively inhibited influenza virus infection.